3D atom probe study of gas adsorption and reaction on alloy catalyst surfaces I: Instrumentation - Bagot, P; de Bocarme, T; Cerezo, A; Smith, G (2006)
A versatile gas reaction cell has been developed for a 3D atom probe system to provide a new method for studying the reaction mechanisms of heterogeneous catalysis. We describe the features and advantages of this new system. The reaction cell enables exposure of metal specimens in high temperature (≤873 K) and high pressure (≤1 bar) environments to a wide range of single gases or gas mixtures. Following treatment, specimens are transferred into the UHV analysis chamber of the 3D atom probe, which provides atomic-scale positional and chemical information for adsorbed gas and metal atoms/oxides from selected regions of the specimen apex. Results demonstrating the effects of heating alloy catalysts in vacuo and in air are presented, which validate the instrument design, alongside a sample of data for exposing Pt and Pt-Rh alloys to NO, revealing the power of the 3D atom probe technique in this field. © 2006 Elsevier B.V. All rights reserved.